Impacts of the Use of Facebook on Foreign Language Learning among Malagasy High School Students in Analamanga - Andrianjary Myriam; Rahanetra Dina; Rakotoson Olivia; Fidelio Arnold; Ratiarimananjatovo Narindra; Ratsimandisa Haritiana Zo; Rakotomalala Nivomboahangy Razanamiarisoa; Koto-te-Nyiwa Ngbolua; Robijaona Rahelivololoniaina Baholy (Britain International for Academic Research (BIAR) Publisher, 2024)
In an increasingly interconnected world, digital tools are rapidly revolutionizing the methods of teaching and learning foreign languages. In Madagascar, a nation undergoing continuous development, the use of the social platform Facebook is emerging as a powerful catalyst for practicing foreign languages such as French and English for secondary school students. In the digital era, where geographical boundaries are losing significance and learning opportunities are endless, the question emerges: